From America to Anatolia: a perspective on oenotourism within the context of sustainable practices and applications - Sinan Bayar; Büsra Kaya; Volkan Altintas (Millenium)
Introduction: Oenotourism, a rapidly growing niche in the tourism industry, plays a crucial role in promoting sustainability and preserving cultural heritage.